2020
DOI: 10.1093/gbe/evaa142
|View full text |Cite
|
Sign up to set email alerts
|

PRE-1 Revealed Previous Unknown Introgression Events in Eurasian Boars during the Middle Pleistocene

Abstract: Abstract Introgression events and population admixture occurred among Sus species across the Eurasian mainland in the Middle Pleistocene, which reflects the local adaption of different populations and contributes to evolutionary novelty. Previous findings on these population introgressions were largely based on extensive genome-wide single nucleotide polymorphism (SNP) information, ignoring structural variants (SVs) as an important alternative resource of genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 53 publications
5
13
0
Order By: Relevance
“…SINE was shorter and more complete than LINE. Similar to our previous findings 53 , SINE, especially the PRE1-SS, PRE0-SS, and PRE1a families in SINE/tRNA, displayed the most recent ages and most polymorphic insertions. These polymorphic SINEs contributed nearly 90% of medium-length SVs among different assemblies, especially the L13 subfamilies, with 36.15% that were classified as the youngest SINEs in the pig genome.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…SINE was shorter and more complete than LINE. Similar to our previous findings 53 , SINE, especially the PRE1-SS, PRE0-SS, and PRE1a families in SINE/tRNA, displayed the most recent ages and most polymorphic insertions. These polymorphic SINEs contributed nearly 90% of medium-length SVs among different assemblies, especially the L13 subfamilies, with 36.15% that were classified as the youngest SINEs in the pig genome.…”
Section: Discussionsupporting
confidence: 91%
“…Further exploring the ages of highly homologous subfamilies in SINE classes ( Fig. 1f with an average divergence of 4%, labelled in purple), we found that 3 out of 26 SINE families (PRE1-SS, PRE0-SS, and PRE1a) were recently active and had been proved to be polymorphic within pig breeds in a previous study 53 , and thus can be viewed as the young SINE families.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The task of disentangling the multistage domestication process of suids has involved a number of disciplines (e.g., archaeology, biology, anthropology, genetics). Besides the traditional archaeological approach [256,257], additional insights into population dispersal and introgression events have been gained using modern genetic data [258][259][260][261]. However, the genetic legacy derived from modern organisms provides only a peek into this protracted and reticulated process; additional lines of evidence need to be drawn from palaeogenomic research.…”
Section: Pigsmentioning
confidence: 99%